Laundry Linen Rental Operation Planning with RFID Technology at PT. Think Clean Laundry - Haloho, Kastauli; Indradewa, Rhian; Hadi Nugroho, Sukmo; Dhafi Iskandar , Muhammad (Syntax Corporation, 2024)
This study aims to examine the application of Radio Frequency Identification (RFID) technology in the laundry and linen rental services offered by PT. Think Clean Laundry. The use of RFID is explored as a solution to improve inventory management efficiency and reduce errors in recording, particularly for clients in hospitals, hotels, industries, and transportation. The research employs qualitative methods, focusing on in-depth understanding and analysis of the phenomenon. Data was gathered through observation and interviews to understand the implementation of RFID technology in linen tracking and operational procedures. The results indicate that RFID technology significantly accelerates laundry processes, minimizes the risk of lost items, and improves service quality by enabling real-time tracking and inventory control. Moreover, the company's adherence to Standard Operating Procedures (SOPs) ensures high-quality service, timely pick-up and delivery, and optimal linen stock management, ultimately leading to increased customer satisfaction. In conclusion, the study confirms that RFID technology in laundry services enhances operational efficiency and customer satisfaction. The implications suggest that other businesses in the laundry sector could benefit from adopting RFID to streamline their operations, reduce human errors, and stay competitive in a technology-driven industry.